2016
DOI: 10.1002/acr.22807
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Self‐Efficacy for Managing Chronic Disease Scale: A Scleroderma Patient‐Centered Intervention Network Cohort Study

Abstract: Objective. Self-management programs for patients with chronic illnesses, including rheumatic diseases, seek to enhance self-efficacy for performing health management behaviors. No measure of self-efficacy has been validated for patients with systemic sclerosis (SSc; scleroderma). The objective of this study was to assess the validity and internal consistency reliability of the Self-Efficacy for Managing Chronic Disease (SEMCD) scale in SSc. Methods. English-speaking SSc patients enrolled in the Scleroderma Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 13 publications
5
35
0
Order By: Relevance
“…SEMCD is a six-item scale that assesses domains of self-efficacy. SEMCD has demonstrated reliability and validity in people with chronic health conditions [36, 37]. Participants respond to each item on a 1–10 point scale (1=not confident at all to 10 totally confident) and the final SEMCD score is the mean of the six items.…”
Section: Methodsmentioning
confidence: 99%
“…SEMCD is a six-item scale that assesses domains of self-efficacy. SEMCD has demonstrated reliability and validity in people with chronic health conditions [36, 37]. Participants respond to each item on a 1–10 point scale (1=not confident at all to 10 totally confident) and the final SEMCD score is the mean of the six items.…”
Section: Methodsmentioning
confidence: 99%
“…The score for the scale is the mean of all items, with higher scores reflecting greater self-efficacy. The SEMCD scale has been validated in patients with SSc 33…”
Section: Methodsmentioning
confidence: 99%
“…In general, these aspects have mostly been neglected, and while several trials have used some self-reported measures as secondary endpoints to measure treatment efficacy, such as the short form (SF-36) health survey or the Euro quol questionnaire (EQ-5D), more focused and structured PROs have seldom been used in SSc. Recently, the Self-Efficacy for Managing Chronic Disease (SEMCD) scale has been validated in SSc [ 130 ] and indeed, it will be of interest to compare therapy responses by scales created by the physician’s judgment with those indexes that take into account fatigue, physical discomfort and pain, emotional distress, interference of health problems in daily life activities and independence. More specific PROs that assess specific domains (gastrointestinal, circulatory to name a few) have been validated and can be used to gauge disease progression and response to therapy from the patient’s perspective [ 9 ]; however, more specific instruments to capture the complexity of the disease or that combine clinical and patient-based endpoints are needed.…”
Section: Classification Of Disease: Who To Fit Wherementioning
confidence: 99%